L’entretien d’un animal essentiel : rapports entre les traités et la pratique dans l’hippiatrie italienne du 13e siècle - Irina Mattioli (Cahiers d’histoire)
Jordanus Rufus’s De Medicina Equorum (1250-1260), written at the court of Emperor Frederick II, is considered the earliest known work on veterinary medicine of Western Culture. Rufus’s treatise has been studied for its innovative approach, its fortune all over Europe, and its influence as indisputable auctoritas until at least the 16° century. However, the work has never been linked to contemporary evidence of daily-life use. In this regard, at the Archive of the Commune of Perugia, relevant evidence exists (1276-1292). This paper argues that the same hippiatric expertise can be found in Rufus’s work and in the documents of Perugia. Such a shared veterinary culture sheds new light on both horse management and on the circulation of specialist knowledge in 13° century Italy. What emerges is that animals, a key-element of technical progress throughout history, also appear, at the time, to be an indirect but significant drive of scientific and cultural innovation.